Spectral, Molecular Modeling, and Biological Activity Studies on New Schiff’s Base of Acenaphthaquinone Transition Metal Complexes - Khlood S. Abou Melha; Gamil A. Al-Hazmi; Ismail Althagafi; Arwa Alharbi; Ali A. Keshk; Fathy Shaaban; Nashwa El-Metwaly (Bioinorganic Chemistry and Applications)
The newly synthesized Schiff’s base derivative, N-allyl-2-(2-oxoacenaphthylen-1(2H)-ylidene)hydrazine-1-carbothioamide, has been characterized by different spectral techniques. Its reaction with Co(II), Ni(II), and Zn(II) acetate led to the formation of 1 : 1 (M:L) complexes. The IR and NMR spectral data revealed keto-thione form for the free ligand. On chelation with Co(II) and Ni(II), it behaved as mononegative and neutral tridentate via O, N1, and S donors, respectively, while it showed neutral bidentate mode via O and N1 atoms with Zn(II). The electronic spectra indicated that all the isolated complexes have an octahedral structure. The thermal gravimetric analyses confirmed the suggested formula and the presence of coordinated water molecules. The XRD pattern of the metal complexes showed that both Co(II) and Ni(II) have amorphous nature, while Zn(II) complex has monoclinic crystallinity with an average size of 9.10 nm. DFT modeling of the ligand and complexes supported the proposed structures. The calculated HOMO-LUMO energy gap, ΔEH-L, of the ligand complexes was 1.96–2.49 eV range where HAAT < Zn(II) < Ni(II) < Co(II). The antioxidant activity investigation showed that the ligand and Zn(II) complex have high activity than other complexes, 88.5 and 88.6%, respectively. Accordingly, the antitumor activity of isolated compounds was examined against the hepatocellular carcinoma cell line (HepG2), where both HAAT and Zn(II) complex exhibited very strong activity, IC50 6.45 ± 0.25 and 6.39 ± 0.18 μM, respectively.